Protection Of Indigenous Peoples In The Perspective Of Human Rights In Indonesia: Realities, Problems And Solutions - Zidane Haikal Senoaji; Anang Setiyawan; Siska Diana Sari (Activa Yuris: Jurnal Hukum, 2021)
The 1945 Constitution upholds the human rights of every citizen without exception, but in practice this constitutional mandate is not implemented properly and even tends to marginalize indigenous peoples. For this reason, it is necessary to seek a constitutional settlement to be able to provide the rights of indigenous peoples as they should be guaranteed in the constitution. This paper is a sociolegal research. The conclusion of our study is that there are still many violations of the constitutional rights of indigenous peoples from a human rights perspective that the government should not do. The recommendation of our study is that the government immediately ratify the Draft Law on Indigenous Peoples as a concrete step in upholding the constitutional rights of indigenous peoples